TVET Systems’ Response to COVID-19 : Challenges and Opportunities - Hoftijzer, Margo; Levin, Victoria; Santos, Indhira; Weber, Michael (World Bank, Washington, DC, 2020)
This note focuses on the role of Technical and Vocational Education and Training (TVET) in the response to the COVID-19 pandemic. It provides guidance on reducing the adverse impact of the pandemic on TVET provision and enhancing the contribution TVET can make to mitigating the health, social, and economic impact of COVID-19.